2022
DOI: 10.3390/buildings12071008
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Damage Characteristics of Granite under Uniaxial Disturbance Loads

Abstract: To investigate the mechanical properties and damage characteristics of granite under frequent disturbance loads in the process of underground engineering construction, laboratory uniaxial compression tests were conducted on granite under combined dynamic and static loading conditions. The following conclusions were reached: (1) under a dynamic disturbance, the failure stress of granite grows gradually as the initial stress and disturbance load rise due to the coupling of damage and strain-rate effect; (2) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition, the reduction of the elastic longitudinal wave velocity inside rock implied the rock damage and this damage was spatially unevenly distributed. The combined dynamic and static loading tests on the samples were carried out respectively from the perspectives of magnitude of pre-static load and amplitude of disturbance load to study the rock burst phenomenon, rock characteristic stress, crack development and rock failure mode (Tao et al (2018), Fei et al (2022), Feng et al (2018), Wang et al (2022)). Liu et al (2022) conducted a dynamic disturbance triaxial loading test on red sandstone samples via disturbance servo triaxial loading system and found that the disturbance load would cause a sudden rise of rock strain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reduction of the elastic longitudinal wave velocity inside rock implied the rock damage and this damage was spatially unevenly distributed. The combined dynamic and static loading tests on the samples were carried out respectively from the perspectives of magnitude of pre-static load and amplitude of disturbance load to study the rock burst phenomenon, rock characteristic stress, crack development and rock failure mode (Tao et al (2018), Fei et al (2022), Feng et al (2018), Wang et al (2022)). Liu et al (2022) conducted a dynamic disturbance triaxial loading test on red sandstone samples via disturbance servo triaxial loading system and found that the disturbance load would cause a sudden rise of rock strain.…”
Section: Introductionmentioning
confidence: 99%